Comparison of the Effectiveness of Self-Care Training and Self-Compassion Training on Hope in Kidney Transplant Patients - Saeedi, Maryam; Zarbakhsh Bahri, Mohammadreza; khaneh Keshi , Ali (KMAN Counseling & Psychology Nexus, 2025)
The aim of this study was to compare the effectiveness of self-care training and self-compassion training on hope in kidney transplant patients. The research design was a quasi-experimental pretest-posttest design with a control group and follow-up. The statistical population included all kidney transplant patients who visited Razi Hospital in Rasht during the first quarter of 2024 to consult with urology and dialysis physicians for treatment follow-up. The total number of patients was 176. The study sample consisted of 45 individuals (15 in the self-care group, 15 in the self-compassion group, and 15 in the control group). The instrument used in this study was the Hope Scale by Snyder et al. (1991). The self-care training sessions were conducted in 8 weekly 60-minute sessions, and the self-compassion intervention was administered in 8 weekly 60-minute sessions based on Gilbert’s protocol (2014) in the experimental groups. Repeated measures ANOVA and Bonferroni post-hoc test were used for data analysis. The results indicated that the overall hope scores in both the self-care and self-compassion groups were higher in the posttest and follow-up phases compared to the pretest, in contrast to the control group. Comparison of means showed that self-compassion training was more effective than self-care training in increasing the level of hope. Moreover, a statistically significant difference was found between the self-care group and the control group (p < 0.01), and between the self-compassion group and the control group (p < 0.05), indicating the effectiveness of both self-care and self-compassion training on hope. Overall, it can be concluded that both interventions—self-care and self-compassion—had positive effects on hope, quality of life, and self-confidence in kidney transplant patients. However, differences were observed in the effectiveness of the two interventions. In general, the findings suggest that combining self-care and self-compassion interventions is recommended for achieving optimal outcomes in improving the condition of kidney transplant patients.